2020
DOI: 10.1001/jamaoncol.2020.2091
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes Associated With 3 Years vs 1 Year of Adjuvant Imatinib for Patients With High-Risk Gastrointestinal Stromal Tumors

Abstract: IMPORTANCEAdjuvant imatinib is associated with improved recurrence-free survival (RFS) when administered after surgery to patients with operable gastrointestinal stromal tumor (GIST), but its influence on overall survival (OS) has remained uncertain.OBJECTIVE To evaluate the effect of adjuvant imatinib on OS of patients who have a high estimated risk for GIST recurrence after macroscopically complete surgery. DESIGN, SETTING, AND PARTICIPANTSIn this open-label, randomized (1:1), multicenter phase 3 clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 14 publications
(31 reference statements)
2
112
0
3
Order By: Relevance
“…The SSGXVIII/AIO trial, which was an open-label, multicenter, randomized, phase III study, showed that 3 years of adjuvant imatinib improved the recurrence rate and overall survival of GIST patients who were at a high risk of recurrence. Therefore, adjuvant therapy with imatinib for at least 3 years is the standard treatment for patients with high-risk GIST[ 15 ]. Our patient initially had a 4.5 cm GIST located in the stomach, with a mitotic rate of 5 mitoses per HPF, and therefore, the patient was classified into the intermediate-risk group; thus, adjuvant imatinib therapy was not administered.…”
Section: Discussionmentioning
confidence: 99%
“…The SSGXVIII/AIO trial, which was an open-label, multicenter, randomized, phase III study, showed that 3 years of adjuvant imatinib improved the recurrence rate and overall survival of GIST patients who were at a high risk of recurrence. Therefore, adjuvant therapy with imatinib for at least 3 years is the standard treatment for patients with high-risk GIST[ 15 ]. Our patient initially had a 4.5 cm GIST located in the stomach, with a mitotic rate of 5 mitoses per HPF, and therefore, the patient was classified into the intermediate-risk group; thus, adjuvant imatinib therapy was not administered.…”
Section: Discussionmentioning
confidence: 99%
“…Auf dem ASCO-Kongress, und direkt anschließend als Vollpublikation, wurden die Daten zum 10-Jahres-Follow-up der SSGXVIII/AIO-Studie publiziert [14]. Die Studie hatte bei Patienten mit hohem Rezidivrisiko eine Therapie mit Imatinib über 1 Jahr mit einer 3-jährigen Therapiedauer verglichen.…”
Section: Langzeitdaten Zur Adjuvanten Therapieunclassified
“…In der deutschen APOLLON-Studie [5] Mit der AIO/SSG XVIII-Studie, in die nur Patienten mit hohem Risiko eingeschlossen wurden, konnte die Überlegenheit einer 3-jährigen Therapie gegenüber der 1-jährigen Gabe sowohl im progressionsfreien als auch im Gesamtüberleben gezeigt werden. 2020 wurden die Daten zum 10-Jahres Follow-up der Studie publiziert [8]. Das Gesamtüberleben in der "intention-to-treat"-Population lag nach 10 Jahren für die Gruppe mit 1-jähriger Therapie bei 65 % und nach 3 Jahren Therapie bei 79 %.…”
Section: Neoadjuvante Therapie Mit Imatinibunclassified